Identifying Hazard and Risk Assessment to Installation of Maintenance Access Platform 1,19 Ton using HIRARC Method - Ajiawan Dwi Nugroho (POLITEKNIK NEGERI BENGKALIS, 2023)
Occupational Safety and Health Management System (OSHMS) is an important factor that every company should be aware of to prevent work accidents. One of the most common methods used in managing OSHMS is HIRARC (Hazard Identification, Risk Assessment, and Risk Control). The method is used in this study with the aim of obtaining potential hazards present on the installation work of the maintenance access platform and the value of the risk. The research procedure is carried out using purposive sampling techniques, with criteria of workers directly involved in the installation of maintenance access platform. A total of 5 respondents consisted of HSE officer, project engineer, rigger and 2 scaffolders. Once the respondent is selected, the questionnaire is created to collect data on the risk value of each respondent. The results found in the study showed that there were 53 potential hazards from 9 jobs and 18 activities. Of the 53 potential hazards, 16 categories are classified as low risk, 25 categories as medium risk, 8 categories as high risk, and 4 categories as very high risk